Multifactor-dimensionality reduction reveals interaction of important gene variants involved in allergy - Guia, Roldan M. de; Echavez, M. D. J.; Gaw, E. L. C.; Gomez, M. R. R.; Lopez, K. a. J.; Mendoza, R. C. M.; Rapsing, J. M. C.; Retreta, D. P.; Tubog, C. M. B.; Ventolero, M. H.; Yao, C. L.; Ramos, J. D. A. (International journal of immunogenetics, 2015)
Elevated IgE levels in the atopic triad of asthma, allergic rhinitis and atopic dermatitis is a multifactorial condition whose genetic component involves interaction of several gene loci. One hundred and two matched pairs of allergic and nonallergic individuals were phenotyped for total serum IgE level using enzyme-linked immunosorbent assay (ELISA). Atopic status was defined by serum IgE concentration ≥100 IU mL−1. SNPs genotyped include the IL4 -590C>T (rs2243250), FCER1B E237G (rs569108), CD14 -159C>T (rs2569190), IL4RA Q551R (rs1801275) and ADRB2 R16G (rs1042713). Gene-gene interaction was analysed using multifactor-dimensionality reduction (MDR). Significant association between atopic allergy and the IL4 -590C>T polymorphism was confirmed in three genetic models. Interaction among the 5 gene variants was validated by MDR. The five-locus model was chosen as the best to describe the interaction of the SNPs within the context of atopy. The strongest interaction was between IL4 -590C>T and IL4RA Q551R and between FCER1B E237G and ADRB2 R16G. The IL4 variant also interacts synergistically with the FCER1B and ADRB2 coding variants. CD14 -159C>T, in general, interacts antagonistically with the rest of the SNPs. In conclusion, a five-locus interaction exists among IL4 -590C>T, FCER1B E237G, CD14 -159C>T, IL4RA Q551R and ADRB2 R16G in Filipino cases of atopic allergy.
Gesehen am 23.12.2020